(untitled) (Asian Journal of Agriculture, 2024)
Abstract. Romadhona S, Soedarmo SPK, Mussadun. 2025. Evaluation of land potential for organic farming development and implications for achieving Sustainable Development Goals (SDGs) in Sleman District, Yogyakarta, Indonesia. Asian J Agric 9: 69-83. The land potential is a critical factor in managing and utilizing land for agriculture. Land with high potential can support quality crop growth, increase production yields, and contribute to food security. Identifying and mapping land potential helps farmers and policymakers make informed decisions to optimize land use, increase production efficiency, and minimize negative environmental impacts. This research highlights the importance of land potential analysis in land use optimization for the agricultural sector in Sleman District, which has a strategic role in the regional economy and community welfare. Using quantitative descriptive analysis and scoring techniques, this research identifies high-potential land for agriculture capable of producing quality crops and high productivity. An overlay approach of multiple maps was used to generate comprehensive new information on land potential, providing essential insights for more efficient and sustainable agricultural decision-making and planning. The novelty of this research lies in integrating scoring and map overlay methods in the analysis of land potential, which has yet to be widely applied in the local context, thus making a new contribution to the literature on agricultural land management in the region. The results of this study identified land potential in Sleman based on the Land Potential Index (IPL) classification. The highest land potential class (IPL) covers 45,741 hectares or 79.77% of the total land area and is spread across all sub-districts. The very high IPL class covers 7,239 hectares or 12.62%, spread across Moyudan, Minggir, Seyegan, Godean, Gamping, Mlati, Depok, Berbah, Prambanan, Kalasan, Ngemplak, Ngaglik, Candi, and Pakem. The medium IPL class covers 3,772 hectares (6.57%), while the low class is only 583 hectares (1.01%). This data shows that most areas have high land potential, essential for planning sustainable agricultural development.